Parental vaccine hesitancy toward routine childhood immunizations and COVID-19 vaccines in Japan: A cross-sectional study - Aya Saitoh; Yugo Shobugawa (BMC Public Health)
Abstract Background This study aimed to elucidate the prevalence and characteristics of parental vaccine hesitancy towards routine infant immunizations and COVID-19 vaccines in Japan. Methods A web-based survey was conducted among 3,227 parents of children aged 0–11 years to assess vaccine-related hesitancy for routine infant immunizations and COVID-19 vaccines for children using the Parent Attitudes about Childhood Vaccines (PACV) questionnaire. Data were collected from January 18 to 25, 2023. Covariates included demographic characteristics, economic status, COVID-19 infection status, decisional conflict scale, and the fear of COVID-19 Scale. Results Vaccine hesitancy was found to be 52.4% for routine infant immunizations and 73% for COVID-19 vaccines. Significant differences in parental attitudes were observed between general childhood vaccines and COVID-19 vaccines for 12 out of 13 PACV survey items. The COVID-19 vaccines showed higher hesitancy rates in 10 items; largest discrepancies were noticed in schedule adherence (22.5% vs 61%), overall hesitancy (40% vs 55.1%), and trust in pediatric doctors (37.2% vs 53.6%). Safety concerns were high for both vaccine types, exceeding 50%. Multivariable analysis identified decisional conflict (RR: 1.01 95% CI: 1.00–1.02) and COVID-19-related fear (RR: 1.04, 95% CI: 1.02–1.05) as hesitancy predictors for routine immunizations. Conclusion Vaccine-related hesitancy for COVID-19 was significantly higher than that for routine immunizations, with decisional conflict emerging as a primary predictor for both. Fear of COVID-19 was associated with routine immunization-related hesitancy. These findings provide critical insights for future pandemic preparedness and vaccine acceptance strategies, highlighting the importance of strengthening trust between healthcare providers and parents, providing clear and reliable information, and implementing decision support tools.